German academic communication in discourse practices: gender policy - I. S. Redkova; N. I. Chernova; N. V. Katakhova (Российский технологический журнал, 2020)
This article focuses on gender discourse genesis in the context of both a new feminist movement and the emergence of feminist linguistics. The process of feminist linguistic theory conversion into the feminist social and political practices has also been revealed in the paper. German universities committed to all-European academic cultural tradition differed greatly from other European educational institutions by the number of women in the academic community. The low women representation in German academic environment is due to the following several factors:- academic institutions do not compete with each other for future students;- professionalization of science, achievements in scientific researches have caused the high status of a scientist in the German society, as well as the prestige of the academic career;- the academic career has become attractive for social elites;- the university boom has led to a dramatic increase of the number of female students and the number of women in the academic staff as well.These have resulted in the re-evaluation of a woman’s place and role in the society including the language structures and reflected by the academic discourse practices and notably in the so called geschlechtsgerechte Sprache, i. e. “equity in languages” principles.